Consumer Protection of Personal Data in the Era of the Industrial Revolution - Haryadi, Wida Ramona (Journal of Legal and Cultural Analytics, 2024)
The thesis entitled Consumer Protection of Personal Data in the Era of the Industrial Revolution written to analyze how Consumer protection of Personal Data listed on the Privacy Policy of a social media. The type of research that the author uses in normative legal research, namely legal research that places law as a building system of norms. The system of norms in qeustion are in  regarding the principles, norm, rules of laws and regulations, court decisions, agreement and doctrines (teachings). The research results obtained are, First, to be protected and feel secure in the protection of personal data in the privacy policy contained in the SNS not to be disseminated without the permission of the owner of the personal data. to avoid selling consumer information to third parties, which has the potential for cybercrime such as: scams, phishing, password leaks, hacked and profiling. Second, The intervention that can be carried out by the State is to make laws and regulations to protect a person's personal data from a privacy policy that is not in accordance with existing norms.